Microbial production of beneficial indoleamines (serotonin and melatonin) with potential application to biotechnological products for human health - Danilovich, Mariana Elizabeth (2021)
Micro-organisms have showed the ability to produce biologically active compounds associated with neurotransmission in higher organisms. In particular, serotonin- and melatonin-producing microbes are valuable sources for the development of eco-friendly bioproducts. Serotonin and melatonin are indoleamines that have received special attention due to their positive effects on human health. These biomolecules exert a critical role in several physiological or pathological processes, including some mental and neurological disorders. This article includes a review of the microbial production of serotonin and melatonin, their functions in micro-organisms and their potential uses as therapeutic and/or preventive agents to improve human health. A description of the quantification methods employed to detect indoleamines and the evidence found concerning their microbial production at laboratory and industrial scale—for application in biotechnological products—is also provided. The microbial ability to synthesize beneficial indoleamines should be further studied and harnessed, to allow the development of sustainable bioprocesses to produce foods and pharmaceuticals for human health.